Arenas of charisma: memory and devotion to Abūnā Bshara Abou Mourad in the construction of the Greek Catholic community in Lebanon (Antropolítica - Revista Contemporânea de Antropologia, 2024)
This article examines the production and mobilization of the charisma of the Greek Catholic monk-priest Bshara Abou Mourad within the Lebanese context. Known as Abūnā (Father) Bshara, this monk plays a central role in the Greek Catholic community, particularly due to his ongoing canonization process in the Vatican, which, if successful, would make him the only saintly representative of this confession. The study investigates the transmission of his charismatic memory and devotional practices in the Lebanese localities associated with his ecclesiastical journey: Joun, Zahle, and Dayr al-Qamar. Drawing on a Weberian concept of charisma, focused on the individual’s extraordinary qualities, but expanding this approach to include its embodiment in objects, images, and its territorial diffusion, the article argues that, in various spaces within these municipalities—designated as “arenas of charisma”—the spiritual power of Abūnā Bshara plays a crucial role in shaping the Greek Catholic community in Lebanon. This phenomenon not only manifests within these arenas but also extends to a national and even regional scale, functioning as a symbol of identity for the confession in contrast to other communities in Lebanon’s multiconfessional and sectarian landscape. Thus, by analyzing charisma across multiple scales (local, national, and regional) and through various perspectives (memorial, devotional, and sectarian), this article contributes to the theory of charisma and its broader implications.